2021
DOI: 10.1001/jamanetworkopen.2021.5477
|View full text |Cite
|
Sign up to set email alerts
|

Utilization Rates of Pancreatectomy, Radical Prostatectomy, and Nephrectomy in New York, Ontario, and New South Wales, 2011 to 2018

Abstract: IMPORTANCE Few studies have compared surgical utilization between countries or how rates may differ according to patients' socioeconomic status.OBJECTIVE To compare population-level utilization of 3 common nonemergent surgical procedures in New York State (US), Ontario (Canada), and New South Wales (Australia) and how utilization differs for residents of lower-and higher-income neighborhoods. DESIGN, SETTING, AND PARTICIPANTSThis cohort study included all adults aged 18 years and older who were hospitalized fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…Many international comparisons have used aggregated data from the World Health Organization or the Organisation for Economic Cooperation and Development (OECD) and revealed that the United States spends more on healthcare and has worse outcomes than other high income countries 345. However, these studies typically lack the granularity to understand why certain countries appear to perform better and why others fall short 6…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many international comparisons have used aggregated data from the World Health Organization or the Organisation for Economic Cooperation and Development (OECD) and revealed that the United States spends more on healthcare and has worse outcomes than other high income countries 345. However, these studies typically lack the granularity to understand why certain countries appear to perform better and why others fall short 6…”
Section: Introductionmentioning
confidence: 99%
“…We established the International Health Systems Research Collaborative (IHSRC: https://projects.iq.harvard.edu/ihsrc/people) to enable comparisons of high income countries (the US, Canada, England, Netherlands, Israel, and Taiwan) using a different approach. The IHSRC uses nationally representative patient level data from participating countries to identify patients with the same diagnoses or undergoing the same procedures to compare processes of care, outcomes, and measures of efficiency across countries 678. The six IHSRC countries were chosen because all have highly developed healthcare systems and accessible administrative data, but differ in their financing, organisation, and overall performance in international rankings 39…”
Section: Introductionmentioning
confidence: 99%
“…Many procedures are sensitive to the preferences of physicians and patients, such as the cost and relative availability of alternative treatments, and there may be greater capacity for discretionary care within the private sector and for other types of low-value procedures. 6 , 27 Furthermore, the majority of elective procedures occur within the private sector. For example, we found the rate of low-value knee arthroscopic debridement was higher in patients without private insurance in public hospitals, although the majority of overall knee arthroscopic procedures (including low-value procedures) are performed in private hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying and curtailing low-value care will curb unnecessary spending and improve quality and outcomes of care . Rates of low-value care have been found to vary between treating facilities and are associated with patient characteristics (eg, gender, age), access to services (eg, availability and frequency of specialist consultations), and physician treatment preferences . Identifying health system factors influencing the provision of low-value care can provide opportunities to reduce this unnecessary care.…”
Section: Introductionmentioning
confidence: 99%
“…A study with a cohort of under 65 years of age in the US found insurance type to be a predictor of ablation [17] and a study using data from Swedish health registries showed that university education and income in the highest quintile were factors associated with undergoing ablation [18]. More recently, a study comparing surgical utilisation in NSW and other countries showed that residents of lower-income neighbourhoods had lower rates of surgery compared to residents of higherincome neighbourhoods [23]. Our work similarly highlights disparities in receiving CA associated with patient status and the neighbourhood index of social advantage and disadvantage, raising concerns on the equitable delivery of CA in Australia.…”
Section: Impact Of Health System Factors On Receiving Ablationmentioning
confidence: 99%